Nutrition and IBD: Malnutrition and/or Sarcopenia? A Practical Guide. (3rd January 2017) - Scaldaferri, F.; Pizzoferrato, M.; Lopetuso, L. R.; Musca, T.; Ingravalle, F.; Sicignano, L. L.; Mentella, M.; Miggiano, G.; Mele, M. C.; Gaetani, E.; Graziani, C.; Petito, V.; et al.
Abstract : Malnutrition is a major complication of inflammatory bowel disease (IBD). This mini review is focusing on main determinants of malnutrition in IBD, the most important components of malnutrition, including lean mass loss and sarcopenia, as an emerging problem. Each one of these components needs to be well considered in a correct nutritional evaluation of an IBD patient in order to build a correct multidisciplinary approach. The review is then focusing on possible instrumental and clinical armamentarium for the nutritional evaluation.